Cost-effectiveness of point-of-care viscoelastic haemostatic assays in the management of bleeding during cardiac surgery: protocol for a prospective multicentre pragmatic study with stepped-wedge cluster randomised controlled design and 1-year follow-up (the IMOTEC study) - Bertrand Rozec; Isabelle Durand-Zaleski; Jean-Christophe Rigal; Elodie Boissier; Karim Lakhal (BMJ Open)
Introduction During cardiac surgery-associated bleeding, the early detection of coagulopathy is crucial. However, owing to time constraints or lack of suitable laboratory tests, transfusion of haemostatic products is often inappropriately triggered, either too late (exposing to prolonged bleeding and thus to avoidable administration of blood products) or blindly to the coagulation status (exposing to unnecessary haemostatic products administration in patients with no coagulopathy). Undue exposition to transfusion risks and additional healthcare costs may arise. With the perspective of secondary care-related costs, the IMOTEC study (Intérêt MédicO-économique de la Thrombo-Elastographie, dans le management transfusionnel des hémorragies péri-opératoires de chirurgies Cardiaques sous circulation extracorporelle) aims at assessing the cost-effectiveness of a point-of-care viscoelastic haemostatic assay (VHA: RoTem or TEG)-guided management of bleeding. Among several outcome measures, particular emphasis will be put on quality of life with a 1-year follow-up.Methods and analysis This is a multicentre, prospective, pragmatic study with stepped-wedge cluster randomised controlled design. Over a 36-month period (24 months of enrolment and 12 months of follow-up), 1000 adult patients undergoing cardiac surgery with cardiopulmonary bypass will be included if a periprocedural significant bleeding occurs. The primary outcome is the cost-effectiveness of a VHA-guided algorithm over a 1-year follow-up, including patients’ quality of life. Secondary outcomes are the cost-effectiveness of the VHA-guided algorithm with regard to the rate of surgical reexploration and 1-year mortality, its cost per-patient, its effectiveness with regard to haemorrhagic, infectious, renal, neurological, cardiac, circulatory, thrombotic, embolic complications, transfusion requirements, mechanical ventilation free-days, duration of intensive care unit and in-hospital stay and mortality.Ethics and dissemination The study was registered at Clinicaltrials.gov and was approved by the Committee for the Protection of Persons of Nantes University Hospital, The French Advisory Board on Medical Research Data Processing and the French Personal Data Protection Authority. A publication of the results in a peer-reviewed journal is planned.Trial registration number NCT02972684; Pre-results.